History of the Development of Pala Agrotourism in the Banda Islands District from 2005 to 2024 - Jamila Lasatu; Najirah Amsi; Rahma Temarwut (ARRUS Journal of Social Sciences and Humanities, 2025)
The Banda Islands, located in Maluku Province, Indonesia, are historically known as the “Spice Islands” due to their central role in the global nutmeg trade. Nutmeg (Myristica fragrans Houtt.) is not only a key economic commodity but also an essential part of the cultural identity and historical heritage of the local community. This study employs a qualitative approach using historical research (historiography) methods to examine the development of nutmeg agro-tourism in the Banda Islands District from 2005 to 2024. Historical research systematically reconstructs past events through stages of heuristics, verification, interpretation, and historiography, enabling an understanding of the social, economic, and cultural dynamics influencing agro-tourism development. Tourism serves as a significant driver of economic growth, generating social and cultural benefits when properly managed. The development of nutmeg agro-tourism in Banda Besar highlights the region’s historical legacy while promoting community income and regional revenue. Traditional post-harvest processing practices and local cultural expressions further enrich the tourism experience, strengthening the integration of heritage preservation and sustainable economic development in the Banda Islands.